Understanding the Ghosts of 20th Century Troubadours; Romanticising Tragedy as a Means of Grieving a Time Before Our Own - Casey, Pippa (Scenari, 2021)
There is a temporal grief in understanding music from a time beyond our own. It’s an obscure sorrow which is often garnered through glorifying and romanticising the demise of certain voices, creating a posthumous narrative which feeds into a societal attraction to the finite, to catastrophe, and to tragedy. This paper will explore triadic contexts of three musicians lost to the 20th century (Jackson. C. Frank, Nick Drake, Jeff Buckley), pertaining to the environments in which their music was created, the tragedies which remain, and the unravelling of 21st century consumption. This thereby identifies a moral paradox: whilst we, the lovers and listeners, survive tragedies belonging to others, we risk understanding music as peripheral to tragedy in doing so. Yet without romanticising tragedy, many voices may have completely faded away alongside the physical bodies and souls which harboured them. So as observers of sacrifice, where do we stand?